Synthesis method of polyacid-based film composite material for removing methylene blue in water
By loading CoPMoV in PVDF, the problem of long removal time and poor performance of methylene blue in the prior art is solved, and rapid and effective removal of methylene blue in water is achieved.
Patent Information
- Application Number
- CN202510048214.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
When removing methylene blue in water, the prior art has a long degradation and adsorption time, and the catalyst function is single and the membrane filtration performance is poor, making it difficult to achieve rapid and efficient removal.
By loading CoPMoV in PVDF, a polyacid-based film composite material was prepared, and the ultra-high methylene blue removal efficiency was used to quickly remove methylene blue in water.
The composite material can quickly and completely remove methylene blue from water, and has excellent degradation function and filtration function, high degradation efficiency, good filtration performance and mild reaction conditions.
Smart Images

Figure CN119869621A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pollutant treatment, in particular to a method for synthesizing a polyacid-based film composite material for removing methylene blue from water. Background Art
[0002] Methylene blue is a common cationic dye with poor degradability and high toxicity. As methylene blue is widely used in industrial production, medical treatment, papermaking, cosmetics and other fields, the discharge of wastewater containing methylene blue has increased year by year, and water pollution has become more serious. In addition, methylene blue can easily accumulate in the human body through water or the food chain, irritating the gastrointestinal tract. In severe cases, nausea, vomiting, diarrhea and other poisoning reactions will occur. Therefore, it is very important to effectively remove methylene blue from water.
[0003] Traditional methods for removing methylene blue from water include biological methods, physical methods (adsorption, precipitation, solution extraction, membrane filtration, etc.) and chemical methods (oxidation, reduction, etc.). The membrane filtration method is simple to operate, highly efficient and also has degradability. Methylene blue adsorbents often have a high specific surface area and a uniform pore size distribution. These advantages allow the adsorbent to adsorb methylene blue in the water on its surface to achieve the purpose of adsorption and filtration removal. In recent years, although some catalysts and adsorbent products in the field can achieve better methylene blue degradation and adsorption effects at a lower cost, the degradation and adsorption time is long, and it usually takes 150 minutes or even longer to achieve adsorption and filtration balance. Therefore, it is necessary to provide a new thin film catalyst that is low in cost, easy to operate, and can quickly degrade and filter out methylene blue. Summary of the invention
[0004] The purpose of the present invention is to provide a method for synthesizing a polyacid-based film composite material for removing methylene blue from water, so as to solve the above-mentioned problems in the background technology. The present invention obtains a polyacid-based film composite material with ultra-high methylene blue removal efficiency by loading CoPMoV in PVDF, which can quickly and completely remove methylene blue from water. The polyacid-based film composite material prepared by the present invention has both excellent degradation function and filtration function.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a polyacid-based film composite material, wherein the composite material uses PVDF as a carrier and CoPMoV as a load, and the chemical formula is: x-CoPMoV-PVDF;
[0007] Wherein, x is the loading amount of CoPMoV in the composite material; the loading amount is 0.2-0.9wt.%.
[0008] Preferably, the preparation method of CoPMoV comprises the following steps: mixing a cobalt salt and a phosphomolybdate vanadate in water, and heating the mixture for reaction to obtain the CoPMoV.
[0009] Preferably, the cobalt salt is cobalt chloride hexahydrate; the phosphomolybdate vanadate is HPMoV; the molar ratio of the cobalt salt to the phosphomolybdate vanadate is 1.83:1; and the temperature of the heating reaction is 60°C.
[0010] The second technical solution of the present invention is to provide a method for preparing the above-mentioned polyacid-based film composite material, comprising the following steps:
[0011] Mixing polyvinylidene fluoride (PVDF), a film-forming aid and CoPMoV in an organic solvent and heating to obtain a CoPMoV-PVDF solution;
[0012] The CoPMoV-PVDF solution is coated on a substrate and then peeled off to obtain the polyacid-based film composite material.
[0013] Preferably, the film-forming aid is polyvinyl pyrrolidone; the mass ratio of polyvinylidene fluoride to the film-forming aid is 5:1; the organic solvent is N,N-dimethylformamide; the heating temperature is 60° C. and the heating time is 5 hours.
[0014] Preferably, the stripping is performed by immersing the substrate coated with the CoPMoV-PVDF solution in water to cause the thin film on the substrate to fall off.
[0015] More preferably, the immersion time in water is 5 s.
[0016] The third technical solution of the present invention is to provide an application of the above-mentioned polyacid-based film composite material in removing organic pollutants in water.
[0017] Preferably, the organic pollutant is methylene blue.
[0018] Technical solution 4 of the present invention: Provide a method for removing methylene blue from water, comprising the following steps:
[0019] The above-mentioned polyacid-based film composite material is added to an aqueous solution containing methylene blue to undergo a degradation reaction, thereby achieving removal of the methylene blue from the water.
[0020] Preferably, before the degradation reaction step, a step of adding an oxidant is also included; the oxidant includes peroxymonosulfate; the ratio of the polyacid-based film composite material, methylene blue and the oxidant is 30mg:0.5mg:13mg.
[0021] More preferably, the degradation reaction temperature is 0-25°C and the pH value is 1-9.
[0022] More preferably, the degradation reaction is carried out at a temperature of 20-25° C., for a time of 5-14 min, and at a pH of 5.
[0023] The beneficial technical effects of the present invention are as follows:
[0024] The present invention obtains a polyacid-based film-based composite material with ultra-high methylene blue removal efficiency by loading CoPMoV in PVDF, and can quickly and completely remove methylene blue in water. The polyacid-based film-based composite material prepared by the present invention has both excellent degradation function and filtration function. The composite material has the advantages of high degradation efficiency, good filtration performance, mild reaction conditions, etc., overcomes the shortcomings of the existing catalyst function being single and the membrane filtration performance being poor, and has good application prospects in sewage treatment. The composite material of the present invention has simple synthesis steps, low synthesis cost, is non-toxic and pollution-free, and is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 IR spectra of CoPMoV, PVDF in Example 1, and the products of Example 1, Example 2 and Example 5.
[0027] Figure 2 The XPS graphs of CoPMoV, PVDF in Example 1, and the products of Example 1, Example 2 and Example 5 are shown.
[0028] Figure 3 This is a graph showing the change in methylene blue removal effect over time when PMS, PVDF, PVDF / PMS, CoPMoV, CoPMoV / PMS, 0.7% CoPMoV-PVDF, and 0.7% CoPMoV-PVDF / PMS are added.
[0029] Figure 4 This is the standard concentration curve of methylene blue.
[0030] Figure 5 This is the result graph of methylene blue adsorption by 0.2% CoPMoV-PVDF, 0.4% CoPMoV-PVDF, 0.6% CoPMoV-PVDF, 0.7% CoPMoV-PVDF, and 0.9% CoPMoV-PVDF.
[0031] Figure 6This is the removal result of methylene blue at different 0.7% CoPMoV-PVDF dosages.
[0032] Figure 7 This is the removal result of methylene blue with different PMS dosages.
[0033] Figure 8 The figure shows the removal results of methylene blue at different pH values.
[0034] Fig. 9 This is the removal result of methylene blue at different reaction temperatures.
[0035] Fig.10 This is a graph showing the effect of 0.7% CoPMoV-PVDF / PMS on the degradation of methylene blue over time. DETAILED DESCRIPTION
[0036] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0037] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0038] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.
[0040] The HPMoV used in the embodiments of the present invention is H5[PMo 10 V2O 40 ], and its synthesis method is:
[0041] Dissolve 2.44 g of sodium metavanadate in 10 mL of boiling water, then add 10 mL of Na2HPO4 aqueous solution (the preparation method of Na2HPO4 aqueous solution is: take 0.71 g of Na2HPO4·12H2O and dissolve it in water, and make up to 10 mL), mix and stir for 10 minutes, then cool to room temperature, then add 0.5 mL of concentrated sulfuric acid, mix evenly, and obtain a red solution A; dissolve 12.1 g of Na2MoO4·2H2O in 20 mL of water to obtain solution B; add solution B to solution A and stir rapidly, then slowly drop 8.5 mL of concentrated sulfuric acid, cool to room temperature, add 50 mL of ether for extraction, collect the middle layer and transfer it to a beaker, add 5 mL of water, heat in a water bath at 60°C and dry, and obtain H5[PMo 10 V2O 40 ](HPMoV).
[0042] The "room temperature" in the present invention is 10-30°C unless otherwise specified.
[0043] According to different methylene blue concentrations and their corresponding absorbances, the relationship between absorbance and concentration is obtained, thereby obtaining the final removal performance of the composite material. The standard curve formula is y=95.54286x+18.28571, see Figure 4 .
[0044] Figure 4 This is the standard concentration curve of methylene blue.
[0045] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.
[0046] Example 1
[0047] A method for preparing a polyacid-based film composite material, comprising the following steps:
[0048] (1) 0.6 g of CoCl2·6H2O was dissolved in 5 mL of distilled water to obtain solution A; 2.4 g of HPMoV was dissolved in 5 mL of distilled water (the molar ratio of CoCl2·6H2O to HPMoV was about 1.83:1) to obtain solution B; solution A was slowly added dropwise to solution B, stirred at room temperature for 2 h to mix evenly, and then placed in an oil bath at 60°C to evaporate to dryness to obtain CoCl2·6H2O. 2.5 [PMo 10 V2O 40 ](CoPMoV).
[0049] (2) 0.09 g of CoPMoV was dissolved in 60 mL of DMF (N, N-dimethylformamide) solution, stirred with a magnetic stirrer until completely dissolved, and then 10 g of PVDF (polyvinylidene fluoride) and 2 g of PVP (polyvinyl pyrrolidone) were added. The mixture was then mechanically stirred in an oil bath at 60 °C for 5 h to obtain a CoPMoV-PVDF solution.
[0050] (3) The CoPMoV-PVDF solution was scraped onto a glass substrate, which was then immersed in distilled water for 5 seconds to allow the film on the substrate to automatically fall off. The film was washed twice with anhydrous ethanol and distilled water alternately to obtain a polyacid-based thin film composite material (denoted as 0.7% CoPMoV-PVDF, the theoretical loading amount of CoPMoV in this composite material was 0.7wt.%, and the actual loading amount was 0.68wt.%). The obtained polyacid-based thin film composite material was cut into a size of 20mm*20mm / piece.
[0051] Example 2
[0052] The only difference from Example 1 is that the amount of CoPMoV in step (2) is adjusted to 0.03 g to obtain the final product (denoted as 0.2% CoPMoV-PVDF, the theoretical loading amount of CoPMoV in the composite material is 0.2wt.%, and the actual loading amount is 0.18wt.%), and the obtained polyacid-based film composite material is cut into a size of 20mm*20mm / piece.
[0053] Example 3
[0054] The only difference from Example 1 is that the amount of CoPMoV in step (2) is adjusted to 0.05 g to obtain the final product (denoted as 0.4% CoPMoV-PVDF, the theoretical loading amount of CoPMoV in the composite material is 0.4wt.%, and the actual loading amount is 0.37wt.%), and the obtained polyacid-based film composite material is cut into a size of 20mm*20mm / piece.
[0055] Example 4
[0056] The only difference from Example 1 is that the amount of CoPMoV in step (2) is adjusted to 0.07 g to obtain the final product (denoted as 0.6% CoPMoV-PVDF, the theoretical loading amount of CoPMoV in the composite material is 0.6wt.%, and the actual loading amount is 0.58wt.%), and the obtained polyacid-based film composite material is cut into a size of 20mm*20mm / piece.
[0057] Example 5
[0058] The only difference from Example 1 is that the amount of CoPMoV in step (2) is adjusted to 0.11 g to obtain the final product (denoted as 0.9% CoPMoV-PVDF, the theoretical loading amount of CoPMoV in the composite material is 0.9wt.%, and the actual loading amount is 0.89wt.%), and the obtained polyacid-based film composite material is cut into a size of 20mm*20mm / piece.
[0059] Comparative Example 1
[0060] The only difference from Example 1 is that the HPMoV in step (1) is replaced by an equal mass of phosphomolybdic acid (chemical formula: H3[PMo 12 O 40 ]), the prepared polyacid-based film composite material is cut into a size of 20mm*20mm / piece.
[0061] Effect verification
[0062] 1. Take a 100mL beaker, add 50mL of 10mg / L methylene blue solution and 1 piece of the composite material synthesized in Comparative Example 1 in sequence, react for 15min under the conditions of 25°C and pH=5, take a sample, and use a UV-visible spectrophotometer to test the absorbance of the solution (664nm); after calculation, the removal rate of methylene blue is only 21.0%.
[0063] Take a 100mL beaker, add 50mL of a 10mg / L methylene blue solution and 1 piece of the composite material synthesized in Comparative Example 1 in sequence, react at 25°C and pH=5 for 1min, then add 13mg PMS (permonosulfate) to the beaker, react for 14min, take a sample, and use a UV-visible spectrophotometer to test the absorbance of the solution (664nm); after calculation, the removal rate of methylene blue is 82.3%.
[0064] The composite material synthesized in Comparative Example 1 has poorer performance than the product data of Example 1 below. This is mainly because compared with single phosphomolybdic acid, the introduction of Co and V bimetallics in CoPMoV can fully activate PMS to generate active species to degrade methylene blue into small molecular non-polluting substances.
[0065] 2. Determine the infrared spectra of CoPMoV, PVDF in Example 1, and x-CoPMoV-PVDF prepared in Example 1, Example 2 and Example 5. The results are shown in Figure 1 .
[0066] Figure 1 IR spectra of CoPMoV, PVDF in Example 1, and the products of Example 1, Example 2 and Example 5.
[0067] from Figure 1It can be seen that in CoPMoV, 954cm -1 、859cm -1 and 740cm -1 The characteristic peaks at 510 cm-1 are attributed to the stretching vibrations of Mo=O (terminal oxygen), Mo-O-Mo (shared corner oxygen) and Mo-O-Mo (shared edge oxygen). -1 、601cm -1 The characteristic peaks at 840cm and 860cm are respectively attributed to the bending vibration of -CF2. -1 、1180cm -1 The characteristic peaks at 1404cm -1 The characteristic peak at 1068cm is attributed to the bending vibration of -CH2. -1 The characteristic peak at 840cm belongs to CC. -1 、1279cm -1 The absorption peak at is attributed to the β-phase vibration of PVDF. In 0.2% CoPMoV-PVDF, 0.7% CoPMoV-PVDF, and 0.9% CoPMoV-PVDF, the above absorption peaks are slightly offset but all appear, which indicates that the polyacid CoPMoV is successfully loaded into the PVDF membrane to make a catalyst.
[0068] 3. XPS of CoPMoV, PVDF in Example 1, and x-CoPMoV-PVDF prepared in Examples 1, 2 and 5 was measured. The results are shown in Figure 2 .
[0069] Figure 2 The XPS graphs of CoPMoV, PVDF in Example 1, and the products of Example 1, Example 2 and Example 5 are shown.
[0070] from Figure 2 It can be seen that in CoPMoV, the absorption peaks at binding energies of 780.5eV, 239.5eV, 517.5eV and 532.5eV are attributed to Co 2p, Mo 3d, V 2p and O1s, respectively. In PVDF, the absorption peaks at 400.1eV and 685.1eV are attributed to N1s and F 1s, respectively. In 0.2% CoPMoV-PVDF, 0.7% CoPMoV-PVDF and 0.9% CoPMoV-PVDF, the absorption peaks of CoPMoV and PVDF appear at binding energies of 780.3eV (Co 2p), 232.1eV (Mo 3d), 518.0eV (V 2p), 532.2eV (O 1s), 688.1eV (F 1s) and 400.1eV (N 1s), respectively. This indicates that CoPMoV and PVDF in each example were successfully composited.
[0071] 4. Take 9 100mL beakers, add 50mL of 10mg / L methylene blue solution to each beaker, and then perform the following treatments:
[0072] Treatment 1 (PMS): 13 mg of PMS was added;
[0073] Treatment 2 (PVDF): Add one piece (A) of single PVDF film (20 mm*20 mm);
[0074] Treatment 3 (PVDF / PMS): Add A single PVDF (20 mm*20 mm) / PMS (13 mg);
[0075] Treatment 4 (CoPMoV): 13 mg of CoPMoV from Example 1 was added;
[0076] Treatment 5 (CoPMoV / PMS): 13 mg CoPMoV and 13 mg PMS were added;
[0077] Treatment 6 (0.7% CoPMoV-PVDF): Add A 0.7% CoPMoV-PVDF film (20 mm*20 mm);
[0078] Treatment 7 (0.2% CoPMoV-PVDF / PMS): Add A 0.2% CoPMoV-PVDF (20 mm*20 mm) and 13 mg PMS;
[0079] Treatment 8 (0.7% CoPMoV-PVDF / PMS): Add A 0.7% CoPMoV-PVDF (20 mm*20 mm) and 13 mg PMS;
[0080] Treatment 9 (Comparative Example 1 product): Add Comparative Example 1 product A (20 mm*20 mm).
[0081] Then the above treatment group was reacted at 25°C and pH = 5 and sampled. The solution absorbance (664nm) was tested using a UV-visible spectrophotometer to compare the removal effect of methylene blue and calculate the removal rate of methylene blue. The results are shown in Table 1 and Figure 3 .
[0082] Table 1
[0083]
[0084] In Table 1, the removal effect of treatment 6 is lower than that of treatment 2. This is mainly because CoPMoV is loaded on the pores of the membrane, the pores become fewer, and the efficiency becomes lower.
[0085] Figure 3This is a graph showing the change in methylene blue removal effect over time when PMS, PVDF, PVDF / PMS, CoPMoV, CoPMoV / PMS, 0.7% CoPMoV-PVDF, and 0.7% CoPMoV-PVDF / PMS are added.
[0086] Figure 3 Among them, CoPMoV-PVDF is 0.7% CoPMoV-PVDF, and CoPMoV-PVDF / PMS is 0.7% CoPMoV-PVDF / PMS.
[0087] from Figure 3 It can be seen that when the material of the embodiment of the present invention is used to treat methylene blue, the removal effect is obvious and better than the existing technology level; comparing the removal effects of different materials, the removal rate of 0.7% CoPMoV-PVDF / PMS can reach 100.0% in 14 minutes, which is the best effect.
[0088] 5. Take 5 100mL beakers, add 50mL of 10mg / L methylene blue solution and 13mg of PMS, and then add A 0.7% CoPMoV-PVDF, 0.2% CoPMoV-PVDF, 0.4% CoPMoV-PVDF, 0.6% CoPMoV-PVDF, 0.9% CoPMoV-PVDF, react and sample at 25℃, pH=5, use UV-visible spectrophotometer to test the solution absorbance (664nm), compare the removal effect of methylene blue, and calculate the removal rate of methylene blue. The results are shown in Table 2 and Figure 5 .
[0089] Table 2
[0090]
[0091] Figure 5 This is the result graph of methylene blue adsorption by 0.2% CoPMoV-PVDF, 0.4% CoPMoV-PVDF, 0.6% CoPMoV-PVDF, 0.7% CoPMoV-PVDF, and 0.9% CoPMoV-PVDF.
[0092] From Table 2 and Figure 5It can be seen that within 28 minutes, each embodiment can achieve a removal rate of 100.0%; but 0.7% CoPMoV-PVDF has a higher methylene blue removal rate than other composite materials with polyacid loading at 14 minutes, and the removal rate has reached 100.0%. However, when the loading is 0.9%, the HPMoV will be leached and cannot be fully loaded on the membrane, resulting in waste; in order to ensure a high removal rate at the lowest cost, the subsequent optimal catalyst is selected as 0.7% CoPMoV-PVDF, which reflects the high cost performance of the composite material.
[0093] 6. The present invention has been found through experiments that if the oxidant PMS is added at the same time as the catalyst prepared in each embodiment of the present invention, the methylene blue removal effect can be further improved. The relevant test data are as follows:
[0094] Take 6 100mL beakers, add 50mL of 10mg / L methylene blue solution, then add 1 / 4, 1 / 2, 3 / 4, 1, 3 / 2, 2 pieces of 0.7% CoPMoV-PVDF (recorded as 1 / 4A, 1 / 2A, 3 / 4A, A, 3 / 2A, 2A), and then add 13mg of oxidant PMS (permonosulfate) to the beaker for catalytic oxidation removal experiment. The reaction was carried out at 25°C and pH=5. Samples were taken during the reaction, and the absorbance of the solution was tested using a UV-visible spectrophotometer (664nm). The removal effect of methylene blue was compared and the removal rate of methylene blue was calculated. The results are shown in Table 3 and Figure 6 .
[0095] Table 3
[0096]
[0097] Figure 6 This is the removal result of methylene blue at different 0.7% CoPMoV-PVDF dosages.
[0098] From Table 3 and Figure 6 It can be seen that with the gradual increase in the amount of 0.7% CoPMoV-PVDF, the removal effect of methylene blue gradually increases. When the additive dosage of the composite material is A, the removal rate of methylene blue can reach 100.0% in 14 minutes.
[0099] 7. Take 5 100mL beakers, add 50mL of 10mg / L methylene blue solution and A0.7% CoPMoV-PVDF, then add 11, 12, 13, 14, 15mg of oxidant PMS (recorded as 0.22, 0.24, 0.26, 0.28, 0.30g / L), respectively, and react at 25℃, pH=5. Samples are taken during the reaction, and the absorbance of the solution is tested by UV-visible spectrophotometer (664nm), and the removal effect of methylene blue is compared to that of methylene blue, and the removal rate of methylene blue is calculated. The results are shown in Table 4 and Figure 7 .
[0100] Table 4
[0101]
[0102] Figure 7 This is the removal result of methylene blue with different PMS dosages.
[0103] From Table 4 and Figure 7 It can be seen that with the gradual increase in the amount of PMS, the removal rate of methylene blue also shows an upward trend. When the added dosage of the oxidant is 13 mg, the removal rate of methylene blue can reach 100.0%. If the amount of PMS is further increased, the efficiency will decrease because too much PMS will self-quench, thus affecting the degradation efficiency.
[0104] 8. Use HCl or NaOH to prepare methylene blue solutions with pH values of 1, 3, 5, 7, and 9; Take 5 100 mL beakers, add 50 mL of 10 mg / L methylene blue solutions with pH values of 1, 3, 5, 7, and 9, respectively, then add A 0.7% CoPMoV-PVDF and 13 mg PMS, react at 25°C, take samples during the reaction, use a UV-visible spectrophotometer to test the solution absorbance (664 nm), compare the removal effect of methylene blue, and calculate the removal rate of methylene blue. The results are shown in Tables 5 and Figure 8 .
[0105] Table 5
[0106]
[0107] Figure 8 The figure shows the removal results of methylene blue at different pH values.
[0108] From Table 5 and Figure 8 It can be seen that the composite material of the present invention can achieve efficient removal of methylene blue at pH 5, so there is no need to adjust the pH value during the experiment.
[0109] 9. Take 5 100mL beakers, add 50mL of methylene blue solution respectively, then add A0.7% CoPMoV-PVDF and 13mg PMS respectively, adjust the reaction temperature to 0, 5, 10, 15, 20, 25℃, and then react for 14min at pH=5. Samples are taken during this period, and the absorbance of the solution (664nm) is tested using a UV-visible spectrophotometer to compare the removal effect of methylene blue and calculate the removal rate of methylene blue. The results are shown in Table 6 and Fig. 9 .
[0110] Table 6
[0111]
[0112] Fig. 9 This is the removal result of methylene blue at different reaction temperatures.
[0113] From Table 6 and Fig. 9 It can be seen that the degradation efficiency of the composite material of the present invention improves with increasing temperature, and the optimal reaction temperature is 25°C.
[0114] 10. Take a 100mL beaker, add 50mL of 10mg / L methylene blue solution, A0.7% CoPMoV-PVDF, and 13mg PMS, respectively, and react at 25°C and pH=5. During the reaction, take samples and use a UV-visible spectrophotometer to test the solution absorbance (664nm). Compare the removal effect of methylene blue and calculate the removal rate of methylene blue. The results are shown in Table 7 and Fig.10 .
[0115] Table 7
[0116]
[0117] Fig.10 This is a graph showing the effect of 0.7% CoPMoV-PVDF / PMS on the degradation of methylene blue over time.
[0118] From Table 7 and Fig.10 It can be seen that A 0.7% CoPMoV-PVDF, 13mg PMS, at 25°C, pH = 5 conditions, can achieve complete oxidation degradation of methylene blue within 14 minutes.
[0119] The above removal rates of the present invention are all average results of three repetitions.
[0120] 11. The filtration performance of 0.7% CoPMoV-PVDF prepared in Example 1 was determined by vacuum filtration. The test method is as follows: prepare a filtration device (including a standard triangular flask, a standard-mouth sand core filter bottle, a cylindrical glass funnel, an aluminum alloy clip and a vacuum pump), install the standard-mouth sand core filter bottle on the standard triangular flask, ensure that the interface is tight, then place a 20mm*20mm 0.7% CoPMoV-PVDF filter membrane on the standard-mouth sand core filter bottle, align it with the center of the cylindrical glass funnel, clamp the connection between the standard-mouth sand core filter bottle and the cylindrical glass funnel with an aluminum alloy clip, connect the standard sand core filter to the vacuum pump, add 25mL of distilled water to the cylindrical glass funnel, turn on the vacuum pump and pressurize 0.1-0.5MPa for pre-compression, so that the membrane reaches a relatively stable flux, and conduct a distilled water vacuum filtration experiment.
[0121] It was measured that the permeate flux (J1) of distilled water was 796.2 L / h·m after 6 min of passage. 2 .
[0122] After the distilled water vacuum filtration experiment was completed, 13 mg of PMS was placed on the filter membrane, and 25 mL of 10 mg / L methylene blue solution was poured into the cylindrical glass funnel to perform a methylene blue solution vacuum filtration experiment.
[0123] It was measured that the methylene blue solution passed through in 10 minutes with a retention rate of 97.5%.
[0124] After the vacuum filtration experiment of the methylene blue solution was completed, 25 mL of distilled water was poured in. It was measured that the distilled water passed through in 10 minutes, and the permeate flux (J2) was 477.7 L / h·m 2 The final filter recovery rate (FRR) was measured to be 60.0%.
[0125] The calculation formula of FRR is: FRR=J2 / J1*100%.
[0126] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A polyacid-based film composite material, characterized in that: The composite material uses PVDF as a carrier and CoPMoV as a load, and the chemical formula is: x-CoPMoV-PVDF; Wherein, x is the loading amount of CoPMoV in the composite material; the loading amount is 0.2-0.9wt.%.
2. The polyacid-based film composite material according to claim 1, characterized in that: The preparation method of CoPMoV comprises the following steps: mixing cobalt salt and phosphomolybdate vanadate in water, and heating for reaction to obtain the CoPMoV.
3. The polyacid-based film composite material according to claim 2, characterized in that: The cobalt salt is cobalt chloride hexahydrate; the phosphomolybdate vanadate is HPMoV; the molar ratio of the cobalt salt to the phosphomolybdate vanadate is 1.83:1; and the temperature of the heating reaction is 60°C.
4. A method for preparing the polyacid-based film composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The polyvinylidene fluoride, a film-forming aid and CoPMoV are mixed in an organic solvent and heated to obtain a CoPMoV-PVDF solution; The CoPMoV-PVDF solution is coated on a substrate and then peeled off to obtain the polyacid-based film composite material.
5. The preparation method according to claim 4, characterized in that: The film-forming aid is polyvinyl pyrrolidone; and / or, the mass ratio of polyvinylidene fluoride to the film-forming aid is 5:1; and / or, the organic solvent is N,N-dimethylformamide; and / or, the heating temperature is 60° C. and the heating time is 5 hours.
6. The preparation method according to claim 4, characterized in that: The stripping step is to immerse the substrate coated with the CoPMoV-PVDF solution in water to cause the thin film on the substrate to fall off.
7. Use of the polyacid-based film composite material according to any one of claims 1 to 3 in removing organic pollutants from water.
8. A method for removing methylene blue from water, characterized in that: The following steps are involved: The polyacid-based film composite material according to any one of claims 1 to 3 is added to an aqueous solution containing methylene blue to undergo a degradation reaction, thereby achieving removal of the methylene blue from the water.
9. The method according to claim 8, characterized in that Before the degradation reaction step, the step of adding an oxidant is also included; and / or the oxidant includes peroxymonosulfate; and / or the ratio of the polyacid-based film composite material, methylene blue and the oxidant is 30mg:0.5mg:13mg.
10. The method according to claim 8, characterized in that The temperature of the degradation reaction is 0-25°C, and the pH value is 1-9.